PENERAPAN FUNGSI MANAJEMEN PADA PENGELOLAAN BUMDES AWARAPIA MAINAWA DALAM MENGEMBANGKAN EKONOMI MASYARAKAT DESA (Studi Kasus Desa Laburunci Kecamatan Pasarwajo Kabupaten Buton) - Dandy, Dandy; Justawan, Justawan; Sartono, Sartono (Universitas Halu Oleo, 2020)
This study aims to determine wether the application of management functions in BUMDes Awarapia Mainawa can improve the economy of rural communities, especially community users of village BUMDes funds in Laburunci Village, Pasarwajo Sub-District, of Buton Regency. The informant of the study was the village BUMDes Manager and a portion of the Laburunci village community of 5 people. In analyzing research data using qualitative descriptive methods, only describes the results of interview questions while in the field. Based on research, result obtained an increase in the community’s economy only occurs in the use of BUMDes Funds in the field of veil and uniform convection business and clean water treatment Laburunci Village, but in the field of craft business brooch there has been no increase in its economy. For that the authors suggest to users of BUMDes Fnds must maintain economic improvement and develop the results of the their business and be careful in using the funds obtained. The BUMDes Manager must control and at the same time provide a better view of the BUMDes fund user.